Adiponectin and interleukin-6 levels in insulin-treated diabetic rats with experimental periodontitis - Ioanna Xynogala; Eudoxie Pepelassi; Despina Perrea; George Agrogiannis; Alkistis Pantopoulou; Efstratios Patsouris; Ioannis Vrotsos (Sociedade Brasileira de Pesquisa Odontológica, 2012)
The aim of the study was to compare the serum levels of adiponectin and interleukin-6 (IL-6) in insulin-treated diabetic rats with or without periodontitis. Forty male Wistar rats were randomly divided into 2 groups (20 rats each): a) insulin-treated diabetic group (control, DI) and b) insulin-treated diabetic periodontitis group (test, DIP). Diabetes was induced, and insulin treatment was initiated on day 5. On day 16, periodontitis was induced in the DIP group. All rats were euthanized on day 77. Adiponectin and IL-6 were assessed on days 16 and 77. At the end of the experiment, 14 and 11 rats survived in the DI and DIP groups, respectively. Adiponectin levels were statistically significantly higher at the end of the experiment compared with levels on day 16 in the periodontitis group (p < 0.05), but not in the control group. At the end of the experiment, adiponectin levels were statistically significantly higher in the periodontitis group compared with the control group (p < 0.05). Within-group and between-group comparisons of IL-6 levels showed no statistically significant difference. In conclusion, serum adiponectin was increased in insulin-treated diabetic rats with periodontitis in comparison with insulin-treated diabetic rats, while IL-6 levels did not differ between groups.